Retrospective analysis of clinical characteristics and treatment of patients with immune checkpoint inhibitors-induced adrenal insufficiency - Huang, Xiao; Zhang, Lin; Zhang, Chuantao; Wang, Huiyun; Shao, Zhuhai; Liu, Ning; Song, Shanai; Jiang, Man; Hou, Helei (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) are effective against solid tumors but can trigger immune-related adverse events (irAEs), including adrenal insufficiency (AI). Given its impact on treatment efficacy and patient quality of life, understanding the clinical characteristics and outcomes of ICI-induced AI (ICI-AI) is critical.MethodsWe conducted a retrospective analysis of 46 patients diagnosed with ICI-AI at a single center (May 2019–July 2024) and reviewed clinical trials/real-world studies on ICI-AI.ResultsThe cohort included 22 cases of isolated adrenocorticotropic hormone deficiency (IAD), 23 of hypophysitis, and 1 of primary adrenal insufficiency (PAI). Median time to AI onset was 7.8 months (range: 1.5–27.4), with a median of 7 ICIs cycles (range: 1–21). Common symptoms were fatigue, anorexia, and nausea; comorbidities included hypothyroidism (41.3%) and hyponatremia (63%). No ACTH-deficient patients recovered during follow-up, but glucocorticoid replacement alleviated symptoms in most cases (45/46). The objective remission rate for underlying malignancies post-AI was 63%. Concurrent irAEs in other organs were rare (3 cases).ConclusionThe median time to AI onset and ICIs cycles administered are key indicators of AI development. Both IAD and hypophysitis are common secondary AI manifestations; glucocorticoid replacement enables safe ICIs continuation.